How Many Orthopaedic Surgeons Does It Take to Write a Manuscript?: A Vignette-Based Discussion of Authorship in Orthopaedic Surgery. (2nd November 2016) - Agel, Julie; DeCoster, Thomas A.; Swiontkowski, Marc F.; Roberts, Craig S.
Abstract : Abstract: The issue of appropriate authorship designation continues to be a topic of importance because authorship of scholarly work plays an important role in the academic community. It is a recognition of an individual's scholarly work and a factor in academic promotion. The Orthopaedic Trauma Association (OTA) sponsored a minisymposium in 2014 to encourage discussion of the issues that arise in authorship decisions. A residency program director/department chair, a journal editor, a clinical trials coordinator, and a promotions committee member provided viewpoints. In the pages that follow, vignettes are presented along with discussion points to encourage conversation on this topic. Authorship criteria are clearly defined. Authorship based simply on seniority or contribution of cases to clinical trials is inappropriate. Discussion of authorship criteria prior to the initiation of clinical research investigations is a standard that must be met. The International Committee of Medical Journal Editors (ICMJE) guidelines provide a framework for this discussion and should be reviewed by all authors prior to publication. Modifications to published authorship guidelines may be necessary to address some of the scenarios identified here that are not adequately addressed by the existing guidelines.